Obesity and sudden cardiac death: Prevalence, pathogenesis, prevention and intervention - Yao, Yan; Xue, Jia; Li, Bing (Frontiers in Cell and Developmental Biology, 2022)
Obesity and sudden cardiac death (SCD) share common risk factors. Obesity, in and of itself, can result in the development of SCD. Numerous epidemiologic and clinical studies have demonstrated the close relationships between obesity and SCD, however, the underlying mechanisms remain incompletely understood. Various evidences support the significance of excess adiposity in determining the risk of SCD, including anatomical remodeling, electrical remodeling, metabolic dysfunction, autonomic imbalance. Weight reduction has improved obesity related comorbidities, and reversed abnormal cardiac remodeling. Indeed, it is still unknown whether weight loss contributes to decreased risk of SCD. Further high-quality, prospective trials are needed to strengthen our understanding on weight management and SCD.